Water Problems of Central Asia: Solution Mechanisms at the Different Levels of Political Management - Bakhodur S. Saidamirov; Andrey V. Toropygin (Евразийская интеграция: экономика, право, политика, 2019)
Definition of opportunities and mechanisms of political management of a water problem in Central Asia are considered and analyzed the research. Objective of the research — to define and reveal mechanisms of political management of different level in a solution of a water problem of the region. Object of the research — political management of a problem. Subject of the research — initiatives and mechanisms of implementation. Dependent variables are: the political and legal bilateral and multilateral relations concerning solution of water problem, specific mechanisms. Independent variables — global and regional initiatives, activity of “The Caspian Five”. The role of efficiency of solution of a water problem depending on priority opinion on a problem of elite of the states is analyzed. This analysis shows that attempts of a solution of a water problem in the region are carried out within universal programs of development of the Purposes of the millennium and Sustainable development goals, “A water initiative of the EU”. The mechanisms for a solution developed within “A water initiative of the EU (VIES) are of great importance: reforms in the field of water policy in countries of Eastern Europe, the Caucasus and Central Asia (VEKTsA)” and activity of the SPEKA Program. At the same time, the most important tools are bilateral and multilateral initiatives of the countries of Central Asia which intensity and efficiency sharply increased at the new leaders of some countries of the region.